2019
DOI: 10.1111/jog.14137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum apelin‐13 and apelin‐36 concentrations in preeclamptic pregnancies

Abstract: Aim Recent studies suggest that apelin can be a novel potential therapeutic mediator to improve the diagnosis, and treatment of preeclampsia. This study aimed to investigate the association of serum apelin‐13 and apelin‐36 with preeclampsia and to detect their relationship with preeclampsia‐associated perinatal morbidity. Methods Forty‐four women with preeclampsia were included as the study group. Forty‐four healthy pregnant women, at similar gestational week with similar gravidity, formed the control group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
3
12
0
3
Order By: Relevance
“…e results of our study showed a significant decrease in apelin circulating level in the PE group compared to the normal pregnant group. is agrees with the results of Deniz et al [27] and Gürlek et al [28], but contradicted by other studies which detect higher apelin circulating levels in preeclampsia [9,13]. at may be because different studies have investigated different isoforms of apelin [28].…”
Section: Discussionsupporting
confidence: 87%
“…e results of our study showed a significant decrease in apelin circulating level in the PE group compared to the normal pregnant group. is agrees with the results of Deniz et al [27] and Gürlek et al [28], but contradicted by other studies which detect higher apelin circulating levels in preeclampsia [9,13]. at may be because different studies have investigated different isoforms of apelin [28].…”
Section: Discussionsupporting
confidence: 87%
“…However, they did not find any relationship between maternal obesity and apelin levels [216]. Furthermore, it was reported that there was not any association between late-pregnancy maternal apelin levels and the incidence of adverse perinatal outcomes (SGA, FGR, preterm deliveries, and admission to neonatal intensive care units) in either preeclamptic patients or healthy pregnant women [224]. In contrast, Van Mieghem et al reported that they found significantly lower apelin levels in pregnancies complicated with fetal growth restriction [242].…”
Section: Other Gestational Complicationsmentioning
confidence: 96%
“…However, there is a strong negative correlation between blood pressure values and apelin levels [222], and a reverse correlation with BMI [224]. The ROC analyses revealed that apelin has poor reliability as a diagnostic tool in the exclusion of preeclampsia-sensitivity (61-64%) and specificity (61-73%, AUC (0.63-0.67)) [224].…”
Section: Preeclampsiamentioning
confidence: 96%
See 2 more Smart Citations